The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1021/jm3014103
|View full text |Cite
|
Sign up to set email alerts
|

SAR Based Design of Nicotinamides as a Novel Class of Androgen Receptor Antagonists for Prostate Cancer

Abstract: Molecular knowledge of pure antagonism and systematic SAR study offered a direction for structural optimization of DIMN to provide nicotinamides as a novel series of AR antagonists. Nicotinamides with extended linear scaffold bearing sterically bulky alkoxy groups on isoquinoline end were synthesized for H12 displacement. AR binding affinity and molecular basis of antiandrogenic effect establish the optimized derivatives, 7au and 7bb, as promising candidates of second generation AR antagonists for advanced pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Molecular modeling indicated that 4 adopts a “Y”-shape conformation and forms multiple hydrogen bonds with AR backbone in HBP (Zhou et al, 2009 ). Besides, via the SAR studies of the lead compound DIMN, Yang et al have synthesized a series of nicotinamides with extended linear scaffold bearing sterically bulky alkoxy groups on isoquinoline end and identified compounds 5 and 6 (Figure 4 ) as promising candidates of second generation antiandrogen for advanced PCa (Yang et al, 2013 ).…”
Section: Rational Antiandrogen Design To Circumvent Drug Resistance Dmentioning
confidence: 99%
“…Molecular modeling indicated that 4 adopts a “Y”-shape conformation and forms multiple hydrogen bonds with AR backbone in HBP (Zhou et al, 2009 ). Besides, via the SAR studies of the lead compound DIMN, Yang et al have synthesized a series of nicotinamides with extended linear scaffold bearing sterically bulky alkoxy groups on isoquinoline end and identified compounds 5 and 6 (Figure 4 ) as promising candidates of second generation antiandrogen for advanced PCa (Yang et al, 2013 ).…”
Section: Rational Antiandrogen Design To Circumvent Drug Resistance Dmentioning
confidence: 99%
“…Recently, new derivatives [131] of DIMN (60), a potent and well characterised AR antagonist interacting with the LBD were designed and synthesised [132] . Some of these derivatives exhibited higher AR antagonistic activity than DIMN itself and bicalutamide, even with DHT co-treatment, and higher inhibitory effects on LNCaP cells proliferation.…”
Section: Seviteronel (5mentioning
confidence: 99%
“…non anilide-type molecules) is also a promising approach to overcome CRPC, and some AR antagonists bearing a unique skeleton or pharmacophore have been reported. 15,16 These compounds have a basic amino or phenolic hydroxyl group on the aromatic ring as the necessary polar group, instead of the cyano-or nitrophenyl group of the anilide-type antagonists.…”
Section: Figurementioning
confidence: 99%